A quarterly model of the Finnish economy - The Model Project Team of the Research Department (Helsinki, Bank of Finland Institute for Economic Research, 1972)
This is a report on the research project begun in 1970 to construct and simulate an econometric model for Finland. The goals of the project and the structure of the model as well as the reasoning behind the specification of the equations are discussed in the report.
Bibliography: p. [105]
osc 06/12/2019
Loans
Keywords: Finland